18F-PSMA-11 PET/MRI in Prostate Adenocarcinoma With Mucinous Features. (10th May 2022) - Zhao, Qian; Yang, Bo; Dong, Aisheng; Zuo, Changjing
Abstract: Primary mucinous tumors involving the prostate gland are rare. We describe MRI and 18 F-PSMA-11 PET/MRI findings in a case of prostate adenocarcinoma with mucinous features. The prostate tumor showed inhomogeneous hyperintensity on T2-weighted images due to high extracellular mucin content and inhomogeneous 18 F-PSMA-11 uptake with SUVmax of 12.5. This case indicates PSMA PET imaging may be helpful for detection of this uncommon variant of prostate adenocarcinoma.